Fused Deposition Modeling Design Rules for Building Large, Complex Components. Issue 3 (3rd May 2016) - Urbanic, R. J.; Hedrick, R.
ABSTRACT: The Fused Deposition Modeling (FDM) process is a bead deposition based additive manufacturing (AM) process that builds a product from thin layers of molten thermoplastic filaments. The ongoing goal of this research is to develop methodologies for designing and fabricating large complex parts such as complex beta testing prototypes, or sand casting patterns. The unique capabilities of the FDM process are leveraged when designing components and assemblies. Complex geometry can be readily manufactured allowing designers to incorporate non-standard component features, and consider unique solutions; however, there are size, surface finish, and accuracy limitations. Rules are developed to leverage the process characteristics and address the observed limitations. Case studies are presented to highlight the benefits and challenges when using the FDM process. GRAPHICAL ABSTRACT: